"Canadian Experience" discourse and anti-racialism in a "post-racial" society. Issue 2 (25th January 2019) - Ku, Jane; Bhuyan, Rupaleem; Sakamoto, Izumi; Jeyapal, Daphne; Fang, Lin
ABSTRACT: "Canadian Experience" is a paradox for many immigrants in Canada and contributes to their exclusion from the labour market. Through an analysis of Canadian English print media, from 2006 to 2011, we illustrate how "Canadian Experience" discourse places the responsibility of immigrant labour market integration on immigrants themselves and constructs their experiences of exclusion as non-racial. This is theorized as a "post-racial" strategy that relies on anti-racialism (avoidance of racial references) to deny the existence and effects of racism, thereby allowing the Canadian public to maintain its façade of innocence but perpetuates "racism without racists". The discourse de-historicizes postcolonial racial hierarchy and promotes a de-racialized neo-liberal model for immigrant inclusion. This has implications for anti-racism and settlement service provision.